Malaysian qualification framework: A need to revisit - Balasingam, U. (2014)
Education is a tool of empowerment and the betterment of a nation and its citizens. The race to achieve our Malaysian Vision 2020 is premised on a highly developed human capital. Learning, knowledge and education are without boundaries, be it in terms of age, place, time, quality and impact. The purpose of this paper is to attempt to measure the quality of our human potential by evaluating the benchmarks set by the Malaysian Qualification Framework against benchmarks of like qualifications of jurisdiction like England Wales and Ireland and Australia for higher level qualifications of degree and masters just as indicators of our standing when benchmarked internationally. It is the conclusion of this paper that we need to revisit and redefine our qualification descriptors to be sufficiently detailed, pegged at appropriate levels and industry sensitive in its outlook so as to enable proper emphasis on required acquirement and appropriate assessment of key indicators within the set qualification descriptors. We need to ensure that our levels are at least comparable to and stand on par on the requisite requirements at same levels across boundaries with international standards in order to achieve our Vision 2020. It is further suggested that we consider a similar benchmarking exercise and the need for a Malaysian Educational Framework for education from the primary school levels upward as education is incremental, developmental and progressive.